2015
DOI: 10.5433/1679-0359.2015v36n1p327
|View full text |Cite
|
Sign up to set email alerts
|

Milho para ensilagem cultivado nos sistemas de plantio direto e convencional sob efeito de veranico

Abstract: Conduziu-se este trabalho com objetivo de avaliar o efeito de períodos de veranico sobre a produtividade de milho para ensilagem cultivado nos sistemas de plantio direto e convencional. O experimento foi conduzido em esquema de parcelas subdivididas, distribuídas no delineamento de blocos casualizados, sendo que nas parcelas foram avaliados os sistemas de plantio direto e plantio convencional e nas subparcelas, seis períodos de veranicos (2, 6, 10, 14, 18 e 22 dias) aplicados a partir dos 34 dias após o planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
11
1
9
Order By: Relevance
“…These dry matter values were greater than those found by Silva et al (2015b), with adequate soil water availability, and by Moraes et al (2013), with maize and sorghum hybrids used for forage, grain and dual purpose production. Furthermore, the dry matter yield of the crops may reach even higher levels, since there was a response up to the maximum N dose applied.…”
Section: Evaluated Parametercontrasting
confidence: 45%
“…These dry matter values were greater than those found by Silva et al (2015b), with adequate soil water availability, and by Moraes et al (2013), with maize and sorghum hybrids used for forage, grain and dual purpose production. Furthermore, the dry matter yield of the crops may reach even higher levels, since there was a response up to the maximum N dose applied.…”
Section: Evaluated Parametercontrasting
confidence: 45%
“…According to Silva et al (2015), the non-tillage system challenge in the Cerrado region lies in the fact to get the ground cover establishment in March or April with sufficient quantity and rusticity. The Cerrado have a dominant dry weather condition in the winter with short photoperiod, and also high rate of decomposition of the mulch in the summer, providing constant supply of material to the soil until the beginning of the next crop planting.…”
Section: Dry Matter Of Cover Crops and Remaining Dry Mattermentioning
confidence: 99%
“…In this sense, the Direct Seeding System (DSS) has stood since the phytomass production is essential for covering and protecting the soil from erosion, contributing to the soil fertility by proper nutrients cycling and improving water retention in soil and water use efficiency by the crop of maize, compared with the conventional system (Silva et al, 2015). Pittelkow et al (2015) reviewed the literature of 678 studies in 63 countries and suggested that the DSS may result a decline in crop production in the tropical regions, where maize is cultivated, compared to the conventional system.…”
Section: Introductionmentioning
confidence: 99%
“…2013), melhoria na eficiência do uso da água na produção do melão (TEÓFILO et, al. 2012) e de milho sob efeitos de veranicos (SILVA et, al. 2015).…”
Section: Introductionunclassified